PERAN HUKUM DALAM MEWUJUDKAN KEADILAN SOSIAL DI MASYARAKAT - Nurtresna, Robby; Mabsuti, Mabsuti (Bureaucracy Journal : Indonesia Journal of Law and Social-Political Governance, 2024)
This journal article explores the role of law in achieving social justice within society. The primary objective of this study is to analyze how legal frameworks and institutions contribute to the realization of social justice, particularly for marginalized communities. Utilizing a doctrinal legal research methodology, the research collects secondary data through literature review and legal documents. The findings indicate that law serves as a crucial instrument for balancing individual freedoms and societal interests, thereby fostering an environment where justice can thrive. However, the study also highlights the challenges faced in the implementation of legal provisions, as many judicial decisions are often perceived as unjust by segments of society. This perception underscores the necessity for a more equitable legal system that genuinely reflects the principles of justice and fairness. In conclusion, the synergy between law and power is essential for promoting social justice. The article advocates for reforms that enhance the legal system’s responsiveness to the needs of the community, ensuring that justice is not merely an abstract concept but a tangible reality for all members of society